2014
DOI: 10.1158/2159-8290.cd-14-0014
|View full text |Cite
|
Sign up to set email alerts
|

NSD3–NUT Fusion Oncoprotein in NUT Midline Carcinoma: Implications for a Novel Oncogenic Mechanism

Abstract: NUT midline carcinoma (NMC) is an aggressive subtype of squamous cell carcinoma that typically harbors BRD4/3-NUT fusion oncoproteins that block differentiation and maintain tumor growth. In 20% of cases NUT is fused to uncharacterized non-BRD gene(s). We established a new patient-derived NMC cell line (1221) and demonstrated that it harbors a novel NSD3-NUT fusion oncogene. We find that NSD3-NUT is both necessary and sufficient for the blockade of differentiation and maintenance of proliferation in NMC cells.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
238
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 209 publications
(241 citation statements)
references
References 57 publications
2
238
0
1
Order By: Relevance
“…Approximately two‐thirds of NMC cases harbor a BRD4–NUTM1 fusion gene, which has been functionally validated as an oncogenic event 39, 40. In the other one‐third of cases, several fusion partners of NUTM1 have been reported in the Mitelman Database of Chromosome Aberrations and Gene Fusions in Cancer (http://cgap.nci.nih.gov/Chromosomes/Mitelman) and recent papers, such as ACIN1, 41, 42, 43 BCOR1, 44 BRD3, 40 BRD9, 41 BPTF, 45 CIC, 46 CUX1, 42 IKZF1, 42, 47 MXD1, 44 NSD3, 48 SLC12A6, 42 ZNF532, 49 and ZNF618. 42 Although MXD1–NUTM1 fusion has been reported in gastric sarcoma, MXD4 has not been previously reported as a fusion partner of NUTM1.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately two‐thirds of NMC cases harbor a BRD4–NUTM1 fusion gene, which has been functionally validated as an oncogenic event 39, 40. In the other one‐third of cases, several fusion partners of NUTM1 have been reported in the Mitelman Database of Chromosome Aberrations and Gene Fusions in Cancer (http://cgap.nci.nih.gov/Chromosomes/Mitelman) and recent papers, such as ACIN1, 41, 42, 43 BCOR1, 44 BRD3, 40 BRD9, 41 BPTF, 45 CIC, 46 CUX1, 42 IKZF1, 42, 47 MXD1, 44 NSD3, 48 SLC12A6, 42 ZNF532, 49 and ZNF618. 42 Although MXD1–NUTM1 fusion has been reported in gastric sarcoma, MXD4 has not been previously reported as a fusion partner of NUTM1.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in addition to the association of BRD4-NUT and ZNF532 proteins in 797TRex patient cells, we found that the ZNF532 locus is a binding target for BRD4-NUT. Chromatin immunoprecipitation sequencing (ChIP-seq) analysis using anti-NUT antibodies revealed strong enrichment over or adjacent to the ZNF532 locus in a variety of NMC cells, including TC-797, 797TRex, 10-15 (16), and PER-403 (17), all of which harbor a BRD4-NUT fusion, and also 10326 cells, which carry a BRD3-NUT translocation (7) (Fig. 2C).…”
Section: Ep300mentioning
confidence: 99%
“…For example, recent studies have shown that NSD3 engages in a rich repertoire of PPIs with other chromatin readers and remodelers. In a subset of NUT midline carcinoma (NMC) cases, an NSD3-NUT fusion protein, which lacks the NSD3 SET domain, blocks differentiation [148]. The NSD3 N-terminus in the fusion protein interacts with the bromodomaincontaining protein BRD4 to drive oncogenesis, and NSD3-NUT NMC cells are sensitive to the bromodomain inhibitor JQ1.…”
Section: Alternative Druggable Regions Of H3k36 Kmtase Proteinsmentioning
confidence: 99%